The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1002/aic.14851
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ionic strength on bubble coalescence in inorganic salt and seawater solutions

Abstract: Bubble size is of fundamental importance in the flotation process, as it provides the surface area for particle collection. Typically, weak surfactants (frothers) are added to process water to reduce bubble coalescence. Certain inorganic electrolytes, which occur naturally in some flotation process water, have been shown to mimic the role of frothers. The concentration at which bubble coalescence is inhibited, the critical coalescence concentration, was determined in a 5.5-L mechanical flotation cell for a ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 28 publications
5
10
0
Order By: Relevance
“…In general the bubble size decreased as a result of the higher electrolyte content in the water. The results corroborated those of Sovechles and Waters (2015) who showed a critical coalescence ionic strength ranging from 0.22 to 0.28 (dimensionless in Sovechles and Waters). Craig et al (1993) clearly demonstrated that it is not a particular ion which prevents bubble coalescence but a combination of ions, which in its simplest form is made of a cation and an anion.…”
Section: Turbulent Environmentsupporting
confidence: 93%
“…In general the bubble size decreased as a result of the higher electrolyte content in the water. The results corroborated those of Sovechles and Waters (2015) who showed a critical coalescence ionic strength ranging from 0.22 to 0.28 (dimensionless in Sovechles and Waters). Craig et al (1993) clearly demonstrated that it is not a particular ion which prevents bubble coalescence but a combination of ions, which in its simplest form is made of a cation and an anion.…”
Section: Turbulent Environmentsupporting
confidence: 93%
“…Salt addition can decrease the bubble size for the possible reason that bubble coalescence is inhibited by charge repulsion 40 . In our earlier work, microbubbles were produced successfully in the salt solution and exhibited great mass transfer characteristics, 41 which is consistent with previous finding that the bubble size correlated well with ionic strength 42 . However, the ionic strength needed for the formation of microbubble system requires further determination.…”
Section: Introductionsupporting
confidence: 87%
“…However, the ionic strength needed for the formation of microbubble system requires further determination. Additionally, for the effect of ionic strength on multiphase flow characteristics, more attention has been paid to the bubble size and gas holdup rather than interfacial area 39,42 . With the development of process industry, techniques based on microbubble generation will be applied widely in the mineral flotation, which requires a systematic investigation on multiphase flow characteristics of the salt solution.…”
Section: Introductionmentioning
confidence: 99%
“…However, this increase in the cultivation medium pumped into the biogas scrubbing unit resulted in increased in N2 and O2 concentrations regardless of the type of diffuser tested. This can be explained by the superior dissolved gas stripping at higher liquid flowrates, which negatively impacted on the final concentration of CH4 in the upgraded biogas [20]. The biogas quality at a L/G ratios of 1 and 2 fulfilled with the current European biomethane standard regardless of the diffuser configuration [2,18,19] Overall, the results herein obtained confirmed that the metallic diffuser was the best system to purify biogas at the L/G ratios typically implemented in photosynthetic biogas upgrading processes in open photobioreactors.…”
Section: Discussionmentioning
confidence: 99%